2003
DOI: 10.1002/app.11891
|View full text |Cite
|
Sign up to set email alerts
|

Glass‐transition temperatures and rheological behavior of methyl methacrylate–styrene random copolymers

Abstract: Poly(methyl methacrylate-ran-styrene) copolymers were synthesized under monomer-starved conditions by emulsion copolymerization. The glass-transition temperatures (T g 's) of the copolymers were measured by differential scanning calorimetry (DSC) and torsional braid analysis (TBA). The results showed that the methyl methacrylate-styrene random copolymers produced an asymmetric T g versus composition curve, which could not even be interpreted by the Johnston equation with different contributions of dyads to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 10 publications
0
18
0
Order By: Relevance
“…The PS-PMMA random copolymers with various fractions were synthesized by emulsion or suspension polymerization. Previous investigations reported that the random copolymer followed an asymmetric T g versus composition curves, which cannot be adapted by the Fox or Gordon -Taylor equations by the different formation of diad-and triad-sequences [26]. Although Fox equation does not predict an exact value of T g in copolymer, it can estimate T g decreasing tendency with thickness in Fig.…”
Section: Fox Equationmentioning
confidence: 96%
“…The PS-PMMA random copolymers with various fractions were synthesized by emulsion or suspension polymerization. Previous investigations reported that the random copolymer followed an asymmetric T g versus composition curves, which cannot be adapted by the Fox or Gordon -Taylor equations by the different formation of diad-and triad-sequences [26]. Although Fox equation does not predict an exact value of T g in copolymer, it can estimate T g decreasing tendency with thickness in Fig.…”
Section: Fox Equationmentioning
confidence: 96%
“…and , glass transition of the investigated copolymers is weakly expressed, stretches over a wide temperature range and without a clear completion exceeds into endothermic peak. Since the glass transition is a relaxation process , in accordance with conventional means of analysis , it can be defined by several temperature values (Fig. ).…”
Section: Resultsmentioning
confidence: 99%
“…). Nonlinear dependence of T g on the composition of copolymers (copolymers that display a maximum or a minimum T g for a certain copolymer share) usually is described by equations : 1Tnormalg=w1P11Tg11+w2P22Tg22+w1P12+w2P21Tg12 Tnormalg=Tg11n11+Tg12(n12+n21)+Tg22n22 1Tnormalg=w1P11Tg11+w2P22Tg22+w1αP12+w2αP21Tg12 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Heat deflection temperature ( HDT ) is a widely employed parameter for quality control and material development in industry and can be taken as the material’s ultimate use point. In order to improve the HDT , NPMI derivatives and their copolymers have attracted considerable interest with respect to applications in acrylonitrile butadiene styrene (ABS) [15] and poly(vinyl chloride) (PVC) [16,17]. Jianting Dong and his co-workers [11,12,13,14,15] synthesized an N -phenylmaleimide (NPMI)-styrene(St)-maleic anhydride (MAH) copolymer (NSM copolymer), and found that the Vicat softening point temperature of the ABS/NSM blend was significantly enhanced by increasing the NSM content.…”
Section: Introductionmentioning
confidence: 99%